2020
DOI: 10.1002/hbm.25126
|View full text |Cite
|
Sign up to set email alerts
|

Structural correlates of atypical visual and motor cortical oscillations in pediatric‐onset multiple sclerosis

Abstract: We have previously demonstrated that pediatric‐onset multiple sclerosis (POMS) negatively impacts the visual pathway as well as motor processing speed. Relationships between MS‐related diffuse structural damage of gray and white matter (WM) tissue and cortical responses to visual and motor stimuli remain poorly understood. We used magnetoencephalography in 14 POMS patients and 15 age‐ and sex‐matched healthy controls to assess visual gamma (30–80 Hz), motor gamma (60–90 Hz), and motor beta (15–30 Hz) cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 52 publications
2
9
1
Order By: Relevance
“…3 ). In Arpin et al (2017) PMBR power was diminished in patients versus controls, while the visuo-motor task showed reduction in visual gamma and a reduction in PMBR amplitude associated with peak latency in patients vs controls ( Waldman et al, 2020 ). Barrett et al (2017) demonstrated a reduction in visual gamma power on stimulation, and a lag in PMBR in patients vs controls.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…3 ). In Arpin et al (2017) PMBR power was diminished in patients versus controls, while the visuo-motor task showed reduction in visual gamma and a reduction in PMBR amplitude associated with peak latency in patients vs controls ( Waldman et al, 2020 ). Barrett et al (2017) demonstrated a reduction in visual gamma power on stimulation, and a lag in PMBR in patients vs controls.…”
Section: Resultsmentioning
confidence: 98%
“…Three studies looked at motor events ( Arpin et al, 2017b , Barratt et al, 2017 , Waldman et al, 2020 ) whilst three studies looked at visual responses ( Barratt et al, 2017 , Stickland et al, 2019 , Waldman et al, 2020 ). Since Barrett et al and Waldman et al undertook visuomotor tasks, these are presented together.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These facts indicate that MRI signal of myelination do not necessarily imply histopathologically complete myelination. Diffusion tensor imaging is reportedly useful in the evaluation of demyelination disease (34) or leukodystrophy (35). More advanced methods for assessment of myelination such as diffusion tensor imaging may help clarify minute abnormalities in myelination in patients with MCT8 deficiency.…”
Section: Myelination In Patients With Mct8 Deficiencymentioning
confidence: 99%